Angiographic appearance of spontaneous coronary artery dissection with intramural hematoma proven on intracoronary imaging. Issue 2 (21st July 2015) - Saw, Jacqueline; Mancini, G.B. John; Humphries, Karin; Fung, Anthony; Boone, Robert; Starovoytov, Andrew; Aymong, Eve
Abstract : Background: The pathognomonic appearance of multiple radiolucent lumen on angiography is used to diagnose spontaneous coronary artery dissection (SCAD). However, this finding is absent in >70% of SCAD, in which case optical coherence tomography (OCT) or intravascular ultrasound (IVUS) is useful to assess arterial wall integrity. Methods: We report the angiographic appearance of SCAD that were proven on intracoronary imaging with OCT or IVUS. Our angiographic classification and algorithm for SCAD diagnosis was previously reported. Patients with type 1 SCAD (multiple radiolucent lumen) do not require OCT/IVUS, whereas, it was recommended for those with suspected type 2 (diffuse stenosis) or 3 (mimic atherosclerosis) SCAD. Results: Twenty‐two consecutive patients with non‐type 1 angiographic SCAD in 25 coronary arteries (22 OCT and 4 IVUS) were studied. Mean age was 52.9 ± 9.9 years, 89.5% were women, and 16/22 (72.7%) had underlying fibromuscular dysplasia. Sixteen SCAD arteries were type 2 SCAD, and nine were type 3. All 25 SCAD arteries had intramural hematoma and intimomedial membrane separation with double lumen on OCT or IVUS. The mean visual angiographic stenosis was 74.6 ± 17.5% (range 40–100%). Dissected segments were long with mean qualitative coronary analysis (QCA) length 45.2 ± 29.2 mm, especially in patients with type 2 SCAD (mean QCA length 58.3 ± 29.0 mm). The mean QCA length in type 3 SCAD lesions was 22.1 ± 5.7 mm. Conclusions: Intracoronary imaging confirms that SCAD may appear angiographically without multiple radiolucent lumen. Angiographers should be familiar with angiographic SCAD variants to improve SCAD diagnosis, and utilize intracoronary imaging when the diagnosis is uncertain. © 2015 Wiley Periodicals, Inc.